Legal Protection of Domestic Workers Who Victims of Domestic Violence in Banyumas Regency - Shofwatun, Fikriyana (UMPurwokerto Law Review, 2021)
Protection of domestic workers who are victims of domestic violence is essential, considering victims’ physical and psychological suffering due to the perpetrator’s actions. Law No. 23 of 2004 concerning the Elimination of Domestic Violence and Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia Number 2 of 2015 concerning the Protection of Domestic Workers become judges’ legitimacy in enforcing the law against perpetrators of violence against household workers. This study aimed to 1) Knowing and analyzing legal protection against domestic workers who experience domestic violence in Banyumas Regency; 2) Knowing the obstacles in the implementation of legal protection against domestic workers in Banyumas Regency. The method used is juridical normative, namely through a literature study that examines secondary data in-laws and regulations and other legal documents and research results, assessment results, and other references complemented by interview results. The results of this study indicate that 1) Protection of household workers who experience household violence in Banyumas Regency is carried out through assistance by the Integrated Service Center- Handling and Protection of Victims of Gender-Based Violence and Children (PPT-PKBGA) where the Heads of (PPT-PKBGA) facilitates the settlement. Through mediation between employers and domestic workers as well as strive to fulfill their rights for household workers. 2) the obstacles in implementing legal protection for household workers in Banyumas Regency are the lack of public knowledge about the law; lack of courage for domestic workers to report cases of violence they have experienced; as well as the people’s view that the problem of domestic violence is personal so that it does not need to be taken out of the household. The advice given is to carry out the law’s socialization on the Elimination of Household Violence (UU-PKDRT) No. 23 of 20014 and Regulation of the Minister of Manpower and Transmigration No. 2 of 2015 concerning Protection of Household Workers. Keywords: Protection, Household Workers, Violence.